A Narrative Systematic Review of Sequential Mediation Models in Education: Linking School Principal Leadership and Parental Support to Student Achievement - Marry Marry; Disman Disman; Dadang Dahlan; Susanti Kurniawati; Li Na (Yayasan Adra Karima Hubbi, 2026)
Background. This study stems from the urgent need to comprehensively understand the various contextual factors that contribute to student academic achievement, particularly through the synergy between school leadership and parental involvement within the framework of a sequential mediation model. Purpose. This study aims to systematically synthesize and analyze various empirical findings related to the implementation of sequential mediation models in an educational context, linking school principal leadership, parental support, and student achievement. Method. The approach used was a systematic narrative review involving the examination of relevant, reputable scientific articles, selected based on predetermined inclusion and exclusion criteria, which were then analyzed thematically to identify patterns of relationships among variables. Results. The study findings indicate that effective school principal leadership serves as an independent variable that drives increased parental participation and support, which ultimately has a positive impact on student achievement as the dependent variable. Conclusion. Therefore, it can be concluded that strengthening educational leadership integrated with parental involvement within a sequential mediation framework is an effective strategy for improving the quality of student learning outcomes.